2021
DOI: 10.1155/2021/2140465
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Analysis Based on Automatic Image Segmentation of DCE-MRI for Predicting Triple-Negative and Nontriple-Negative Breast Cancer

Abstract: Purpose. To investigate whether quantitative radiomics features extracted from dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) could be used to differentiate triple-negative breast cancer (TNBC) and nontriple-negative breast cancer (non-TNBC). Materials and Methods. This retrospective study included DCE-MRI images of 81 breast cancer patients (44 TNBC and 37 non-TNBC) from August 2018 to October 2019. The MR scans were achieved at a 1.5 T MR scanner. For each patient, the largest tumor mass was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Recent studies have demonstrated that segmentation repeatability is essential in terms of feature stability, for it is heavily influenced by different MRI protocols and machines [ 21 , 33 , 34 , 35 , 36 ]. In this paper, we downloaded the segmented data outlined on the TCIA website by using automatic image segmentation and manual supervision, and we performed the experiment using the FAE software, which is a publicly available tool for radiomics models and is applied to many fields [ 37 , 38 , 39 , 40 , 41 ]. Thus, all the experiment results are robust and replicable.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that segmentation repeatability is essential in terms of feature stability, for it is heavily influenced by different MRI protocols and machines [ 21 , 33 , 34 , 35 , 36 ]. In this paper, we downloaded the segmented data outlined on the TCIA website by using automatic image segmentation and manual supervision, and we performed the experiment using the FAE software, which is a publicly available tool for radiomics models and is applied to many fields [ 37 , 38 , 39 , 40 , 41 ]. Thus, all the experiment results are robust and replicable.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, DCE is most commonly used in AI diagnostic models ( 33 , 35 , 61 , 62 ). The addition of other sequences, such as DWI, to obtain higher diagnostic specificity has also started to be explored ( 63 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different works were devoted in the last decades to exploring the use of radiomic IFs for different clinical issues. Recently, several studies have explored the application of advanced machine learning methods and deep learning to breast MRI (e.g., [ 60 , 61 ]) publishing a clinical–radiomics model combining a DCE-based radiomics signature and clinical data to predict complete response after neoadjuvant chemotherapy in patients with axillary lymph node metastasis.…”
Section: Biomarkers For Bcmentioning
confidence: 99%